2002
DOI: 10.1029/2002gl014727
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of the fate of gas hydrates during transit through the ocean water column

Abstract: [1] We report on controlled experiments to document the fate of naturally occurring methane hydrate released from the sea floor (780 m, 4.3°C) by remotely operated vehicle (ROV) disturbance. Images of buoyant sediment-coated solids rising ($0.24 m/s) from the debris cloud, soon revealed clear crystals of methane hydrate as surficial material sloughed off. Decomposition and visible degassing began close to the predicted phase boundary, yet pieces initially of $0.10 m size easily survived transit to the surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 15 publications
1
30
0
Order By: Relevance
“…In sandy sediment, the hydrate tends to fill the existing pore structure of the sediment, potentially entraining sufficient sediment to prevent the hydrate/sediment mixture from floating, while in fine-grained sediments, bubble and hydrate grow by fracturing the cohesion of the sediment, resulting in irregular blobs of bubbles (Gardiner et al, 2003;Boudreau et al, 2005) or pure hydrate. Brewer et al (2002) and Paull et al (2003) tried the experiment of stirring surface sediments from Hydrate Ridge using the mechanical arm of a submersible remotely operated vehicle, and found that hydrate did manage to shed its sediment load enough to float. Hydrate pieces of 0.1 m survived a 750 m ascent through the water column.…”
Section: Fate Of Methane Hydrate In the Water Columnmentioning
confidence: 99%
“…In sandy sediment, the hydrate tends to fill the existing pore structure of the sediment, potentially entraining sufficient sediment to prevent the hydrate/sediment mixture from floating, while in fine-grained sediments, bubble and hydrate grow by fracturing the cohesion of the sediment, resulting in irregular blobs of bubbles (Gardiner et al, 2003;Boudreau et al, 2005) or pure hydrate. Brewer et al (2002) and Paull et al (2003) tried the experiment of stirring surface sediments from Hydrate Ridge using the mechanical arm of a submersible remotely operated vehicle, and found that hydrate did manage to shed its sediment load enough to float. Hydrate pieces of 0.1 m survived a 750 m ascent through the water column.…”
Section: Fate Of Methane Hydrate In the Water Columnmentioning
confidence: 99%
“…Changi ng processes can be observed in realtime, and both qualitative and qu antitati v e data can be obtained. The novel in situ spectroscopic tech niques we have devised will enhance m any CO 2 and gas hydrate studies (e.g., Brewer et al, 2002a;Brewer et al, 2002b;Rehder et al, 2002;Rehd er et al, 200 4), and can be extended to a v ery wide r ange of o cean science, inclu ding hydroth ermal vent studies.…”
Section: Comparison With Raman Measurementsmentioning
confidence: 99%
“…where J Ba 2+ is the diffusive flux of Ba 2+ , ϕ the porosity, D sed the tortuosity-and temperature-corrected diffusion coefficient of Ba 2+ in the sediment, calculated from the diffusion coefficient in free solution (D 0 ) of 147.6 cm 2 year -1 (5°C) after Boudreau (1997), and dC/ dx is the concentration gradient of Ba 2+ in pore water. As it is not possible to determine past changes in the upward Ba 2+ gradient, the present-day Ba 2+ gradients recorded at the two sites were used.…”
Section: Calculation Of Barite Precipitation Timementioning
confidence: 99%
“…The mass and distribution of hydrates can change over time when variations in pressure, temperature, and salinity (PTS), as well as in the methane saturation state of the surrounding fluids and in methane fluxes occur. The decomposition of gas hydrates induced by changes in PTS is referred to as dissociation (e.g., Brewer et al 2002); the decomposition of gas hydrates due to methane undersaturation is termed dissolution (e.g., Egorov et al 1999;Rehder et al 2004;Bigalke et al 2009;Lapham et al 2010). Methane undersaturation in marine sediments can be produced through the sulfatedependent anaerobic oxidation of methane (AOM; Lapham et al 2010), which was shown to typically occur above and within gas hydrate-bearing sediments (e.g., Borowski et al 1996Borowski et al , 1999Bohrmann et al 1998;Boetius et al 2000;Dickens 2001b;Treude et al 2003;Orcutt et al 2004;Snyder et al 2007a, b).…”
Section: Introductionmentioning
confidence: 99%